Analisis Pengaruh Volume Kendaraan terhadap Emisi CO₂ (Studi Kasus: Jalan Lintas Sumatera Kabupaten Muaro Jambi) - Emelda Raudhati (Universitas Batanghari, 2026)
High land transportation activity on Sumatra Highway in Muaro Jambi Regency has the potential to increase carbon dioxide(CO₂) emissions and degrade environmental quality. This study aims to analyze the effect of traffic volume on CO₂ emissions along the Sumatra Highway in Muaro Jambi Regency. Traffic Volume data were obtained using the traffic counting method and converted into passengercar units (PCU). CO₂ emissions were estimated using the IPCC Tier 3 approach through Kaya decomposition analysis. The relationship between traffic volume and CO₂ emissions was examined using simple linear regression. The results indicate that the traffic volume reached 63041 vehicle per day, with total CO₂ emissions of 272957,70 g/km. regression analysis shows a very strong positive relationship between traffic volume and CO₂ emissions, with a coefficient of determination (R²) of 0,9509. The linear regression analysis yields the equation Y = 80,018X + 5230,3, indicating a positive linear relationship between vehicle volume and CO₂ emissions. This result demonstrates that an increase in traffic volume is directly proportional to the rise in CO₂ emissions, where higher numbers of vehicles contribute significantly to increased emission levels.